The Representation of Skepticism in Don’t Look Up Film: An Overview of Current Environmental Issue - Halim, Nur Mutmainna; Taufik, Muhammad; Fisdarnianti, Fisdarnianti (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2024)
This article explores the representation of skepticism in the film